2019
DOI: 10.1002/ece3.5830
|View full text |Cite
|
Sign up to set email alerts
|

Identification of winter moth (Operophtera brumata) refugia in North Africa and the Italian Peninsula during the last glacial maximum

Abstract: Numerous studies have shown that the genetic diversity of species inhabiting temperate regions has been shaped by changes in their distributions during the Quaternary climatic oscillations. For some species, the genetic distinctness of isolated populations is maintained during secondary contact, while for others, admixture is frequently observed. For the winter moth (Operophtera brumata), an important defoliator of oak forests across Europe and northern Africa, we previously determined that contemporary popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…However, the lack of predicted presence in these areas could have arisen simply from inadequate sampling in that region. Winter moth was recently reported from Tunisia (Mannai et al 2015), and genetic analyses suggest this population is native to the region (Andersen et al 2019b). Andersen et al (2019b) also reported winter moth occurrence in southern Spain and Italy.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, the lack of predicted presence in these areas could have arisen simply from inadequate sampling in that region. Winter moth was recently reported from Tunisia (Mannai et al 2015), and genetic analyses suggest this population is native to the region (Andersen et al 2019b). Andersen et al (2019b) also reported winter moth occurrence in southern Spain and Italy.…”
Section: Discussionmentioning
confidence: 61%
“…Winter moth was recently reported from Tunisia (Mannai et al 2015), and genetic analyses suggest this population is native to the region (Andersen et al 2019b). Andersen et al (2019b) also reported winter moth occurrence in southern Spain and Italy. Because dates of these observations fall outside of the range of dates that were used for the climate data (1970-2010), they were not used in our analysis, though their inclusion could further change the predicted distribution of winter moth to include additional Mediterranean locations.…”
Section: Discussionmentioning
confidence: 61%
“…Five-hundred and fifty-two individual winter moths were included after removing individuals from which fewer than 20 of 24 polymorphic microsatellites were amplified as part of this study. To that dataset, 249 individuals genotyped in Andersen et al (2017Andersen et al ( , 2019 were added to increase the geographic sampling of winter moth populations.…”
Section: Sampling Strategy Dna Extraction and Microsatellite Amplifmentioning
confidence: 99%
“…Under this approach, dataset(s) are simulated based on scenarios that include several likely regions of origin, and summary statistics from the sample dataset are compared to those from the simulated datasets to determine the most likely scenario. The approach can be used to examine the evolutionary histories of native organisms that have become pests by exploring whether outbreaks are the result of natural range expansion or introductions of novel (and potentially more virulent) populations (e.g., Wei et al 2015, Andersen et al 2019. However, this approach is not without its limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation